Bahamas. Technical cooperation strategy 2011-2014 ﻿ - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2022)
Presents the Bahamas country strategy, which is an instrument that organizes and prioritizes the technical cooperation that the institute provides to the country. It begins with the development of a strategic framework for the agricultural sector and then details the proposed technical cooperation actions, focused on four main projects. Finally, it explains the mechanisms that will be used to evaluate the obtained results